Mind Mapping Method Using Xmind Application to Improve French Speaking Skills - Salsabilla, Ananda Pimpie; Sunendar, Dadang; Amalia, Farida; Ramadini, Febyasti Davela; Fahmi, Royan Nur (Makassar State University, 2024)
Abstract. There are several issues faced by beginner French learners in learning speaking skills. Students are difficult to learn and pronounce French words correctly. They still read texts to perform monologues as well. Meanwhile, they are required to have speaking skills that focus on general situations in daily life. According to these issues, a different approach is needed to improve their language skills. Therefore, this study discusses the utilization of digital-based mind map in improving French speaking skills. The purpose of this study was to determine how the Xmind application is used to create mind map in the classroom and find out the students' speaking skills after the implementation of it. This study uses a pre-experimental method with quantitative approach and One Group Pretest-Posttest design. The participants in this study were students of the French Language Education at one of the universities in Indonesia. The implementation of the mind mapping method by the Xmind application in speaking skills was carried out by creating a monologue with specified theme. According to the results of data analysis, there was an improvement in students' speaking skills after the implementation of the mind mapping method by the Xmind application. This is indicated by an increase in the average score of speaking skills which in the pre-test was 62.2/100 to 83.9/100 in the post-test. Furthermore, the results of the questionnaire analysis showed that there are many advantages of this method implementation. The majority of participants (85.5%) stated that the mind mapping method helped in enhancing vocabulary for speaking French and in general (76.3%), students stated that implementing the mind mapping method by the Xmind application helped them to improve their memory.Keywords: Mind Mapping; French Speaking Skills; Xmind; Learning Method